Meat and livestock markets in West and Central Africa - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1998)
Marchés bétail-viande en Afrique de l'Ouest et du Centre, a new quarterly newsletter